KNOWLEDGE, ATTITUDE, AND PRACTICES ON BIOMEDICAL WASTE MANAGEMENT AMONG MEDICAL INTERNS OF A TERTIARY CARE HOSPITAL IN NORTH KARNATAKA - ATHIRA J SANKAR; AMRUTA SWATI I; SHRUTI KARDALKAR; SHRINIVAS REDDY B (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Every health-care personnel is expected to have adequate knowledge, good attitude, safe practice, and capacity to guide others for appropriate biomedical waste (BMW) collection and management. The study aims to assess the knowledge, attitude and practices regarding BMW management among the budding yet responsible doctors- the medical interns in ESIC Medical College and Hospital, Gulbarga. Methods: A cross-sectional study was conducted among all the 81 interns currently posted in ESIC Medical College and Hospital, Gulbarga. Data were collected using pre-designed and semi-structured questionnaire to assess the knowledge, attitude, and practices on BMW management. Results: The study found that a majority (69.1%) of interns demonstrated fair knowledge regarding BMW management. Majority (93.8–98.8%) of the interns showed a positive attitude towards BMW segregation, self-responsibility, observation of charts at workplace, and training on BMW management. Furthermore, only 12.3% interns viewed BMW management as an extra burden on work. However, only 44.4% of interns were pre-treating liquid waste, and 50.6% were using a needle hub cutter. Alarmingly, 23.3% indicated that they would not report injuries. Conclusion: BMW management practices can be further improved with strict supervision and incorporation of BMW management in the assessment of internship completion in addition to periodic training